Non-Communicable Diseases Deaths Attributable to High Body Mass Index in Chile - De Moraes-Ferrari, G (Nature Research, 2021)
We estimated the proportion and number of deaths from non-communicable diseases (NCD) attributable to high body mass index (BMI) in Chile in 2018. We used data from 5927 adults from a 2016–2017 Chilean National Health Survey to describe the distribution of BMI. We obtained the number of deaths from NCD from the Ministry of Health. Relative risks (RR) and 95% confidence intervals per 5 units higher BMI for cardiovascular disease, cancer, and respiratory disease were retrieved from the Global BMI Mortality Collaboration meta-analyses. The prevalences of overweight and obesity were 38.9% and 39.1%, respectively. We estimated that reducing population-wide BMI to a theoretical minimum risk exposure level (mean BMI: 22.0 kg/m2; standard deviation: 1) could prevent approximately 21,977 deaths per year (95%CI 13,981–29,928). These deaths represented about 31.6% of major NCD deaths (20.1–43.1) and 20.4% of all deaths (12.9–27.7) that occurred in 2018. Most of these preventable deaths were from cardiovascular diseases (11,474 deaths; 95% CI 7302–15,621), followed by cancer (5597 deaths; 95% CI 3560–7622) and respiratory disease (4906 deaths; 95% CI 3119–6684). A substantial burden of NCD deaths was attributable to high BMI in Chile. Policies and population-wide interventions are needed to reduce the burden of NCD due to high BMI in Chile. © 2021, The Author(s).